2020
DOI: 10.1002/jca.21805
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of the impact of recirculation on exchange kinetics in tandem extracorporeal membrane oxygenation and therapeutic plasma exchange

Abstract: Vascular access connection configurations during tandem extracorporeal membrane oxygenation (ECMO) and therapeutic plasma exchange (TPE) may impact exchange kinetics. In these tandem procedures, typically the TPE inlet line is proximal to the TPE return line with respect to blood flow in the ECMO device, maximizing the opportunity for replacement fluid homogenization within the ECMO circuit. However, if TPE inlet and return line connections are switched, recirculation-a phenomenon in which replacement fluid le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…To our knowledge, there are no mathematical models for simulating simultaneous ECMO and plasma exchange besides our previous work [14]. This paper provides mathematical justification for our previous model, extends this approach to both veno-arterial and veno-venous ECMO, and derives a new class of related models.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…To our knowledge, there are no mathematical models for simulating simultaneous ECMO and plasma exchange besides our previous work [14]. This paper provides mathematical justification for our previous model, extends this approach to both veno-arterial and veno-venous ECMO, and derives a new class of related models.…”
Section: Introductionmentioning
confidence: 86%
“…In the typical configuration, the inlet line for the TPE device is upstream from the return line, and in the switched configuration these lines are reversed. A comparison of these two configurations was the focus of our initial modeling effort, and we further study these two configurations in this paper [14]. We also present numerical results comparing different classes of models and different configurations of the TPE device.…”
Section: Introductionmentioning
confidence: 99%
“…Placing the TPE return line distal to the inlet line prevents the possibility of a phenomenon known in dialysis of recirculation (which reduces overall efficacy of a procedure). While the potential for recirculation could occur, one mathematical model demonstrated that when combined with ECMO the risk for recirculation is negligible when TPE return line is proximal to TPE inlet line [35]. In this study, the apheresis instrument inlet and return flow lines were connected to the tubing on the low‐pressure side (proximal to the oxygenator and air trap) of the ECMO circuit, thus placing the apheresis instrument flow in parallel.…”
Section: Tandem Tpe and Ecmomentioning
confidence: 99%
“…In this study, the apheresis instrument inlet and return flow lines were connected to the tubing on the low‐pressure side (proximal to the oxygenator and air trap) of the ECMO circuit, thus placing the apheresis instrument flow in parallel. This configuration is intended to maximize the opportunity for satisfactory homogenization of the replacement fluid within the ECMO circuit [35]. No specific access pressure alarm or negative pressure limit settings were modified on the apheresis instruments in preparation for these procedures.…”
Section: Tandem Tpe and Ecmomentioning
confidence: 99%